Impedance spectroscopy and electro-optic switching times of a liquid crystal-hydroxypropylcellulose network composite - MANAILA MAXIMEAN, DOINA (2019)
This paper presents electric and electro-optic studies conducted on a new composite, namely hydroxypropylcellulose network with liquid crystal fillings. The composite was manufactured using the electrospinning method, and deposited on indium tin oxide glass. In terms of electric characterization, the samples were subjected to impedance spectroscopy, their equivalent circuit model was deduced, and the corresponding electric parameters were computed based on the Cole-Cole diagrams and frequency plots of the two impedance components. In terms of electro-optic studies, the optical transmission of the sample under a varying steady-state alternative regime voltage was recorded, and the saturation threshold field was determined. Also, the switching times of the sample with respect to a step signal were determined.